Chemical communication, aggression, and conspecific recognition in the fish Nile tilapia - Giaquinto, P. C.; Volpato, G. L. (Elsevier B.V., 1997)
The chemical modulation of agonistic behavior and conspecific recognition were tested in juveniles of the fish Nile tilapia, Oreochromis niloticus (L.). After a 7-day isolation period, the fish were grouped (four individuals per aquarium) for 7 days. Then fish of alpha and beta ranks (previously matched for similar size) were paired in a neutral territory for analysis of their agonistic interaction. Pairs composed of alpha and beta fish were established with either fish from the same group (familiar) or from two different groups (unfamiliar). The pairs were tested in contiguous compartments, either with water exchange between the compartments or in the absence of water exchange. In each condition the fish were separated by a transparent glass partition. Twelve pairs were tested in each experimental condition. Fish behavior was videotaped and the following variables were analyzed: (a) frequency of and time spent in agonistic patterns, (b) latency to start fighting, and (c) duration of swimming. Water exchange between compartments decreased agonistic interactions. This effect, however, was more pronounced in pairs of fish coming from the same group (in this case, subordinate fish spent less time in confrontations than dominant ones). We conclude that chemical communication decreases aggression in this species by (1) inducing an alarm reaction and (2) increasing conspecific recognition (thus stabilizing the dominance hierarchy). (C) 1997 Elsevier B.V.
Keywords: chemical communication; recognition; dominance; social hierarchy; confrontation; agonistic behavior; fish; Nile tilapia; Oreochromis niloticus